Deep phenotyping to understand hearing and hearing disorders: Protocol for a feasibility study - Ruth V. Spriggs; Paul Bateman; Raul Sanchez-Lopez; Sally K. Thornton; Olivia R. Phillips; Derek J. Hoare; Ian M. Wiggins (PLoS ONE, 2025)
Globally, hearing loss affects around 1.5 billion people, while tinnitus is estimated to impact around 740 million. More research is urgently needed to address the challenges presented by hearing loss, tinnitus, and other hearing-related conditions. Our plans for a Nottingham Hearing BioResource, providing research-willing volunteers and comprehensive tests of hearing and ear health repeated over time, has the potential to accelerate the field. The protocol described here is a feasibility study for this BioResource, specifically addressing questions of recruitment from the general population (i.e., outside of clinical audiology services or pathways). Participants with or without known hearing problems will be recruited for data collection. This study will quantify how feasible it will be to recruit and retain a large sample of the general population, and will suggest the demographic, and hearing condition status, distributions we could achieve for the BioResource. Data collection will involve a health and lifestyle questionnaire; cognitive assessment; five questionnaires about hearing loss, tinnitus, and hyperacusis; an estimation of lifetime noise exposure; a suite of in-depth audiological tests; and taking a hair sample. The same measurements will be taken on two separate occasions in person, and a third set of overlapping measurements will be taken remotely. Repeating the data collection will allow us to evaluate participant retention rates and establish the reliability of the measures. The findings from this feasibility study will allow us to assess which channels work well to recruit a diverse pool of participants, which, when used in conjunction with recruitment from clinic, will provide the basis for a recruitment strategy for our BioResource. In addition, we will gain useful insight into whether specific tests or questionnaires used in the feasibility study are suitable for inclusion in a deep phenotyping protocol.